Markers of lipid oxidation and inflammation in bronchial cells exposed to complete gasoline emissions and their organic extracts. (October 2021) - Rossner, Pavel; Cervena, Tereza; Vojtisek-Lom, Michal; Neca, Jiri; Ciganek, Miroslav; Vrbova, Kristyna; Ambroz, Antonin; Novakova, Zuzana; Elzeinova, Fatima; Sima, Michal; Simova, Zuzana; Holan, Vladimir; et al.
Abstract: Road traffic emissions consist of gaseous components, particles of various sizes, and chemical compounds that are bound to them. Exposure to vehicle emissions is implicated in the etiology of inflammatory respiratory disorders. We investigated the inflammation-related markers in human bronchial epithelial cells (BEAS-2B) and a 3D model of the human airways (MucilAir™), after exposure to complete emissions and extractable organic matter (EOM) from particles generated by ordinary gasoline (E5), and a gasoline-ethanol blend (E20; ethanol content 20% v/v). The production of 22 lipid oxidation products (derivatives of linoleic and arachidonic acid, AA) and 45 inflammatory molecules (cytokines, chemokines, growth factors) was assessed after days 1 and 5 of exposure, using LC-MS/MS and a multiplex immunoassay, respectively. The response observed in MucilAir™ exposed to E5 gasoline emissions, characterized by elevated levels of pro-inflammatory AA metabolites (prostaglandins) and inflammatory markers, was the most pronounced. E20 EOM exposure was associated with increased levels of AA metabolites with anti-inflammatory effects in this cell model. The exposure of BEAS-2B cells to complete emissions reduced lipid oxidation, while E20 EOM tended to increase concentrations of AA metabolite and chemokine production; the impacts on other inflammatory markers were limited. In summary, complete E5 emission exposure of MucilAir™ induces the processes associated with the pro-inflammatory response. This observation highlights the potential negative health impacts of ordinary gasoline, while the effects of alternative fuel are relatively weak. Highlights: Effects of gasoline and gasoline-ethanol studied in bronchial 2D and 3D models. Assessment of exposure to complete emissions and particulate matter extracts. Analysis of lipid oxidation and inflammation markers after days 1 and 5 of treatment. Pro-inflammatory response in the 3D model was caused by complete gasoline emissions. Limited effects of the gasoline-ethanol blend were observed.